EXPLORING COPING MECHANISMS OF ADOLESCENT SIBLINGS IN DIVERSE FAMILY STRUCTURES - M , M; P., Gunn (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
This study aims to explore the coping strategies of typically developing adolescent siblings of individuals with and without physical disabilities in Pakistan. A total of 100 participants were selected from different special schools in Karachi using purposive sampling. The Coping Strategy Indicator (CSI) was used to measure problem-focused coping, behavior-focused coping, and emotion-focused coping. Results showed that typically developing adolescent siblings of individuals without physical disabilities had coping strategies similar to those of typically developing adolescent siblings of individuals with physical disabilities. Family bonds, specifically sibling bonds, play a crucial role in an individual’s growth and development, especially for individuals with physical disabilities. The study underscores the need for better support in caregiving and institutionalized settings to establish stronger bonds within households with siblings and identifies the importance of providing support to both disabled and non-disabled individuals. Limitations and recommendations for future research are also discussed.